Clinical signs, duodenal histopathological grades, and serum high‐mobility group box 1 concentrations in dogs with inflammatory bowel disease. (4th September 2021) - Lee, Jong‐Hwan; Kim, Hong‐Suk; Lee, Dohee; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Kang, Ji‐Houn; Kang, Byeong‐Teck; Yang, Mhan‐Pyo; Kim, Hakhyun
Abstract: Background: Inflammatory bowel disease (IBD) commonly occurs in dogs, but there is lack of information about potential biomarkers of clinical and histopathologic severity. Objective: To examine the role of serum C‐reactive protein (CRP) and high‐mobility group box 1 (HMGB1) concentrations in dogs with IBD. Animals: Seventeen dogs with IBD and 25 healthy dogs. Methods: In this prospective study, duodenal histopathologic severity was graded, and the clinical severity of IBD was assessed by the canine IBD assessment index (CIBDAI) score in dogs with IBD. Serum CRP and HMGB1 concentrations were compared between IBD and healthy dogs and analyzed according to histopathologic grade in dogs with IBD. The correlations between serum CRP and HMGB1 concentrations and the CIBDAI score were evaluated. Results: Dogs with IBD had higher serum CRP (median [range] = 20.39 [1.53‐67.69] μg/mL vs 2.31 [0.17‐11.49] μg/mL; P  < .001) and HMGB1 concentrations (0.44 [0.07‐1.58] ng/mL vs 0.05 [0.01‐0.25] ng/mL; P  < .001) than healthy dogs. The serum HMGB1 concentration was higher in IBD dogs with a moderate to severe histopathologic grade (0.51 [0.30‐1.58] ng/mL, P  = .03) than in those with a mild histopathologic grade (0.17 [0.07‐0.75] ng/mL). Serum CRP concentrations and CIBDAI score were positively correlated in dogs with IBD ( r s  = .49, P  = .05). Conclusions and Clinical Importance: Serum HMGB1 could be a potential biomarker for diagnosing IBD and might be indicative of histopathologic severity in dogs, whereas serum CRP might be an indicator of clinical severity.